2018
DOI: 10.1159/000485658
|View full text |Cite
|
Sign up to set email alerts
|

Del-1 Expression as a Potential Biomarker in Triple-Negative Early Breast Cancer

Abstract: Objective: A differential diagnostic role for plasma Del-1 was proposed for early breast cancer (EBC) in our previous study. We examined tumoral Del-1 expression and analyzed its prognostic impact among patients with EBC. Methods: Del-1 mRNA expression was assessed in breast epithelial and cancer cells. Meanwhile, the tumoral expression of Del-1 was determined based on tissue microarrays and immunohistochemistry results from 440 patients. Results: While a high Del-1 mRNA expression was found in all the breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…In this study, we demonstrated a significant association between EDIL3 protein expression and Gleason score in prostate cancer. We also found an association between EDIL3 protein expression and tumor grade in breast cancer, as previously reported 23 , and to explore the correlation between EDIL3 expression and overall survival of the patients, we studied the TCGA database where we analyzed the RNAseq in breast cancer patients 28 . We observed a statistical significance in the group of patients with high levels of mRNA of EDIL3 that had a shorter overall survival at 10 years, in a Kaplan–Meier’s survival curve.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In this study, we demonstrated a significant association between EDIL3 protein expression and Gleason score in prostate cancer. We also found an association between EDIL3 protein expression and tumor grade in breast cancer, as previously reported 23 , and to explore the correlation between EDIL3 expression and overall survival of the patients, we studied the TCGA database where we analyzed the RNAseq in breast cancer patients 28 . We observed a statistical significance in the group of patients with high levels of mRNA of EDIL3 that had a shorter overall survival at 10 years, in a Kaplan–Meier’s survival curve.…”
Section: Discussionsupporting
confidence: 56%
“…EDIL3 acts as a pro-angiogenic factor, mediator of the immune and anti-inflammatory response, and a regulator of endothelial cell adhesion and migration [13][14][15] . It has been reported that EDIL3 is overexpressed in several tumor types, including bladder, pancreas, breast, and liver carcinomas, and associates with tumor progression and poor prognosis [16][17][18][19][20][21][22][23] . EDIL3 has been identified as a novel regulator of EMT in hepatocellular carcinoma cells, as the increased expression of EDIL3 by miRNA-137 downregulation triggers ERK and TGF-β activation via interaction with the integrin α V β 3 ( 20 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, EDIL3 is associated with the diagnosis and outcome of patients. High expression of EDIL3 is related to early breast cancer with worse survival trend, especially in triple-negative breast cancer(TNBC) [32], [33], [34]. Moreover, EDIL3 secreted by cellular ingredients of hematopoietic stem cells (HSCs) niche is indispensable to myelopoiesis in both physiologic and pathologic conditions [35].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, EDIL3 has shown to induce EMT in many types of tumor tissues (10)(11)(12)(13)(14). It is overexpressed during the transition from kidney intraepithelial neoplasia to invasive carcinoma and lead to significant increase in proliferation, angiogenesis, invasion and metastasis capacity (15).…”
Section: Developmentally Regulated Endothelial Cell Locus 1 (Del-1 Amentioning
confidence: 99%